Genita wart: therapeutic response with immiquimod and surgery - Fedrizzi, Edison N.; Nahn Junior, Edilbert P.; Passos, Mauro R.L. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Condylomata acuminata is one of the genital manifestations of the Human papillomavirus (HPV) infection in the genital area. This is a case report of a 27 years-old female patient with extensive genital warts in the vulvar. The treatment was performed with surgical ressection of the biggest warts and local application of immiquimod in the others lesions and relapses. The complete clinical resolution was observed in 8 weeks. We will review the different forms of treatment emphasing immiquimod treatment.